2020
DOI: 10.1016/j.jad.2019.09.048
|View full text |Cite
|
Sign up to set email alerts
|

Is prenatal maternal distress context-dependent? Comparing United States and the Netherlands

Abstract: Background: Maternal anxiety and depression symptoms during pregnancy can compromise a woman's wellbeing and affect offspring development. The present study represents a comparison of maternal late-pregnancy internalizing symptoms (i.e., depression and anxiety) between the United States of America (US) and the Netherlands. We hypothesized that women in the US would report higher levels of anxiety and depression during pregnancy compared to their Dutch counterparts, both on individual symptom indicators and ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The health status of primiparas and their mental preparation for pregnancy and delivery after pregnancy are also important factors that affect their emotions [ 14 ]. Prepregnancy underlying diseases and/or postpregnancy complications will increase the risk of adverse pregnancy outcomes and have adverse effects on the life and health of both the pregnant woman and the fetus [ 15 ]. In addition, in the early stage of pregnancy, pregnancy reaction can cause nausea, vomiting, loss of appetite, and other early pregnancy reaction [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The health status of primiparas and their mental preparation for pregnancy and delivery after pregnancy are also important factors that affect their emotions [ 14 ]. Prepregnancy underlying diseases and/or postpregnancy complications will increase the risk of adverse pregnancy outcomes and have adverse effects on the life and health of both the pregnant woman and the fetus [ 15 ]. In addition, in the early stage of pregnancy, pregnancy reaction can cause nausea, vomiting, loss of appetite, and other early pregnancy reaction [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The findings revealed nonsignificant changes in pandemic HCC in two similar Western samples of low‐risk community children and adolescents, suggesting that psychoneuroendocrine processes unfold similarly even in different contexts when exposed to the same stressor. Our initial hypothesis concerning such differences was based on prior work showing a heightened level of maternal distress in the prenatal period (Gartstein et al., 2020) and more reactive temperament in infants (Sung et al., 2015) in the United States compared to the Netherlands, hinting at different stress processes in similar samples from different contexts. It could be the case that such differences fade with age or that these may manifest at a behavioral but not physiological level, as investigated here.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown context‐dependent differences across countries in child cortisol outcomes based on variations in the prenatal and postnatal environment (Desmarais et al., 2021). One study found that pregnant women in the United States experienced heightened levels of psychological distress compared to women in the Netherlands, possibly due to culturally mediated contextual factors, such as less favorable perinatal health care (Gartstein et al., 2020). These findings are significant because perinatal symptoms of anxiety and depression were found to predict altered offspring developmental outcomes, in line with the fetal programming hypothesis (Glover et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Well-being and well-being in HRP are broadly defined as having senses of pleasure, happiness, and satisfaction and consists of physical, functional, emotional, intellectual, psychological, familial, and social aspects [ 11 ]. Well-being improvement and distress reduction during HRP are the keys to achieve positive maternal–fetal outcomes [ 17 19 ]. Therefore, besides physical problems, healthcare providers need to pay close attention to the feelings, satisfaction, and well-being of women during HRP and need to employ appropriate interventions to reduce their problems and improve their well-being [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%